Validation of farmer’s practice of using sodium chloride for controlling foot rot disease of black pepper (Piper nigrum) - BHAI, R SUSEELA; ANANDARAJ, M; SRINIVASAN, V (The Indian Journal of Agricultural Sciences, 2011)
An innovative field observation by a farmer indicated that common salt (sodium chloride) is effective in controlling Phytophthora foot rot of black pepper (Piper nigrum L.) caused by Phytophthora capsici. This is validated through a series of in vitro and in vivo experiments. Initially mycelial growth, sporangial formation and zoospore germination of P. capsici were studied on a range of concentrations from 0.01 M to 3.0 M of NaCl. It was found that mycelial growth is inhibited by 1 M, Sporangial production by 0.75 M and zoospore germination by 0.5 M sodium chloride respectively. But, in vivo studies by challenge inoculation with P. capsici showed that the maximum inhibitory concentration under in vitro (1 M) is insufficient to inhibit P. capsici in the soil. Hence, higher concentrations, viz 2 M to 8 M were tested in soil. The results showed that 3 to 4 M concentrations of sodium chloride are the maximum required to destroy the soil inoculum but was found phytotoxic. Modification of the treatment by washing-off the soil amended with salt resulted in nullifying the phytotoxic effect without affecting the total microbial biomass, nutrient status, pH or electrical conductivity of the soil. This method can be used as a pre- planting practice while rejuvenating a diseased garden or while gap-filling or while raising nursery plants in potting mixture.